A Series of π‐Extended Thiadiazoles Fused with Electron‐Donating Heteroaromatic Moieties: Synthesis, Properties, and Polymorphic Crystals. Issue 7 (22nd December 2014) - Kato, Shin‐ichiro; Furuya, Takayuki; Nitani, Masashi; Hasebe, Naoya; Ie, Yutaka; Aso, Yoshio; Yoshihara, Toshitada; Tobita, Seiji; Nakamura, Yosuke
Abstract π‐Extended thiadiazoles 4–8 fused with various electron‐donating heteroaromatic moieties have been designed and synthesized. Just like thiadiazoles 1–3 synthesized previously, 4–8 exhibit intramolecular charge‐transfer (CT) interactions, moderate‐to‐good fluorescence quantum yields of up to 0.78, and electrochemical amphoterism. In comparison with 1–3, the benzannulation in thiadiazoles 4–7 moderately extends the π conjugation and significantly increases the stability of the cationic species formed upon electrochemical oxidation. The fluorescence quantum yields increase remarkably from 3 to 6 and 7 due to the efficient suppression of nonradiative intersystem crossing resulting from the benzannulation. The properties of 4–8 strongly reflect the different species annulated to the pyrrole rings, namely benzothiophene, naphthalene, and benzofuran. Eleven crystals, including poly‐ and pseudopolymorphic crystals of 1 (1‐Crys.(Y) and 1‐Crys.(G)), 2 (2‐Crys.(O) and 2‐Crys.(G)), 4 (4‐Crys.(O) and 4‐Crys.(G)), and 6 (6‐Crys.(O) and 6‐Crys.(G)), were obtained and characterized by X‐ray crystallography. The fluorescence colors and efficiencies are distinct for each poly‐ and pseudopolymorph of 1, 2, 4, and 6. It has been suggested that both the extent of the electronic interactions in the π‐stacked dimers and the presence of excitonic interactions originating in the 1D face‐to‐face slipped columns affect the fluorescence wavelengths of the poly‐ and pseudopolymorphs.